Facilitating Searches in Multiple Bibliographical Databases: Metadata Harvesting Service Providers - Hirwade, Mangala Anil; Bherwani, Mohini T. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2009)
A metadata harvester is a software package that reads data from servers, writes it to databases, implements various kinds of searches, and writes HTML files to display the results. In this paper sixty metadata harvesting service providers have been studied. The study reviewed metadata generation, preservation and harvesting, and various technical issues arising at these stages.